A novel mathematical model for mixed-feed multi-effect distillation system optimization design - Cong Liu; Rouman Li; Lin Xu; Weiqi Liu (Desalination and Water Treatment)
In this work, a novel mathematical model called State-space Superstructure has been developed for the optimization design of a mixed-feed multi-effect distillation (MED) system. The model takes into account complex feeding arrangement relationships and aims to improve the thermal performance of the system. By using this model, novel mixed-feed arrangements have been obtained, which show improved performance compared to forward-feed arrangements in terms of gained output ratio (GOR) and specific heat transfer area (As). The GOR is increased by 16 % and As is decreased by 18 %. Additionally, the number of evaporators and preheaters can be reduced with these mixed-feed arrangements, resulting in a similar freshwater production capacity as a forward-feed MED system. Three optimal design schemes are studied, showing that there is a positive correlation between GOR and As. Therefore, when optimizing the GOR or As, it is essential to impose constraints on the optimization objective that is not being prioritized. The optimization scheme focusing on As and constraining GOR resulted in an 18 % decrease in As, while the scheme emphasizing GOR and constraining As led to a 10 % increase in GOR. Overall, this novel mathematical model provides insights for improving the design of mixed-feed multi-effect distillation systems.